Interventions to address substance use and sexual risk among gay, bisexual and other men who have sex with men who use methamphetamine: A systematic review. (1st January 2019) - Knight, Rod; Karamouzian, Mohammad; Carson, Anna; Edward, Joshua; Carrieri, Patrizia; Shoveller, Jean; Fairbairn, Nadia; Wood, Evan; Fast, Danya
Highlights: Interventions addressing both meth and sexual risks among gbMSM can be efficacious. Psychosocial interventions show the most promise in reducing meth and sexual risks. Pharmaceuticals have limited efficacy addressing meth and sexual risks among gbMSM. Limited research on meth and sexual risk harm reduction interventions and gbMSM. Abstract: Background: Methamphetamine use is common among some populations of gay, bisexual and other men who have sex with men (gbMSM). This study reviewed the status of research on the efficacy of interventions that address harms among gbMSM who use methamphetamine. Methods: We searched MEDLINE, PsycINFO, CINAHL, Embase, Cochrane Central Register of Controlled Trials, Web of Science, and Google Scholar to identify publications from inception to October 23, 2017, that assessed an intervention addressing methamphetamine use among gbMSM. Results: Of 1896 potential studies and 935 unique articles screened for inclusion, 28 eligible studies assessed 26 different interventions in the following categories: pharmacological ( n  = 5); psychosocial ( n = 20); harm reduction ( n = 1). Given that outcome variables were measured in highly variable ways, we were unable to conduct a meta-analysis of intervention effects. However, 22 studies reported a statistically significant effect on one or more methamphetamine-related outcomes. Among 21 studies that included measures of sexual health-related outcomes, 18 reported a significant effect on one or more sexual health-related outcomes, and 15 of those reported a concurrent effect on both drug- and sexual health-related outcomes. Conclusions: This is the first review to provide compelling evidence that integrating interventions to address both drug- and sexual-related harms for gbMSM who use methamphetamine can be efficacious. Future research should focus on identifying differential effects of various intervention approaches by social positioning, as well as prioritize future evaluations of integrated harm reduction interventions (e.g., the distribution of harm reduction kits within sexual health care settings).